218k views
5 votes
How do I solve: 2 sin (2x) - 2 sin x + 2√3 cos x - √3 = 0

User Liliane
by
5.6k points

1 Answer

5 votes

Answer:


\displaystyle x = (\pi)/(3) +k\, \pi or
\displaystyle x =- (\pi)/(3) +2\,k\, \pi, where
k is an integer.

There are three such angles between
0 and
2\pi:
\displaystyle (\pi)/(3),
\displaystyle (2\, \pi)/(3), and
\displaystyle (4\,\pi)/(3).

Explanation:

By the double angle identity of sines:


\sin(2\, x) = 2\, \sin x \cdot \cos x.

Rewrite the original equation with this identity:


2\, (2\, \sin x \cdot \cos x) - 2\, \sin x + 2√(3)\, \cos x - √(3) = 0.

Note, that
2\, (2\, \sin x \cdot \cos x) and
(-2\, \sin x) share the common factor
(2\, \sin x). On the other hand,
2√(3)\, \cos x and
(-√(3)) share the common factor
\sqrt[3}. Combine these terms pairwise using the two common factors:


(2\, \sin x) \cdot (2\, \cos x - 1) + \left(√(3)\right)\, (2\, \cos x - 1) = 0.

Note the new common factor
(2\, \cos x - 1). Therefore:


\left(2\, \sin x + √(3)\right) \cdot (2\, \cos x - 1) = 0.

This equation holds as long as either
\left(2\, \sin x + √(3)\right) or
(2\, \cos x - 1) is zero. Let
k be an integer. Accordingly:


  • \displaystyle \sin x = -(√(3))/(2), which corresponds to
    \displaystyle x = -(\pi)/(3) + 2\, k\, \pi and
    \displaystyle x = -(2\, \pi)/(3) + 2\, k\, \pi.

  • \displaystyle \cos x = (1)/(2), which corresponds to
    \displaystyle x = (\pi)/(3) + 2\, k \, \pi and
    \displaystyle x = -(\pi)/(3) + 2\, k \, \pi.

Any
x that fits into at least one of these patterns will satisfy the equation. These pattern can be further combined:


  • \displaystyle x = (\pi)/(3) + k \, \pi (from
    \displaystyle x = -(2\,\pi)/(3) + 2\, k\, \pi and
    \displaystyle x = (\pi)/(3) + 2\, k \, \pi, combined,) as well as

  • \displaystyle x =- (\pi)/(3) +2\,k\, \pi.
User Farshid Palad
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.